Genetic diversity among viruses associated with sugarcane mosaic disease in Tucumán, Argentina - Perera, María Francisca (2009)
Sugarcane leaves with mosaic symptoms were collected in 2006--07 in Tucumán (Argentina) and analyzed by reverse-transcriptase polymerase chain reaction (RT-PCR) restriction fragment length polymorphism (RFLP) and sequencing of a fragment of the Sugarcane mosaic virus (SCMV) and Sorghum mosaic virus (SrMV) coat protein (CP) genes. SCMV was detected in 96.6% of samples, with 41% showing the RFLP profile consistent with strain E. The remaining samples produced eight different profiles that did not match other known strains. SCMV distribution seemed to be more related to sugarcane genotype than to geographical origin, and sequence analyses of CP genes showed a greater genetic diversity compared with other studies. SrMV was detected in 63.2% of samples and most of these were also infected by SCMV, indicating that, unlike other countries and other Argentinean provinces, where high levels of co-infection are infrequent, co-existence is common in Tucumán. RFLP analysis showed the presence of SrMV strains M (68%) and I (14%), while co-infection between M and H strains was present in 18% of samples. Other SCMV subgroup members and the Sugarcane streak mosaic virus (SCSMV) were not detected. Our results also showed that sequencing is currently the only reliable method to assess SCMV and SrMV genetic diversity, because RT-PCR-RFLP may not be sufficiently discriminating.